Role of Pathya-Ahara and Yogic Practices in the Management of Type- II Diabetes Mellitus. - Dhiman, Sonia; Nepal, Prashanna; Jagota, Ankush (International Research Journal of Ayurveda & Yoga, 2023)
INTRODUCTION ABSTRACT: Background: Diabetes Mellitus is a metabolic disorder involving inappropriately elevated blood glucose levels. In Ayurvedic texts also, different Acharya have mentioned about twenty types of Prameha and Madhumeha is a type of Vataj Prameha. Madhumeha is correlated with DM because of its characteristic KshaudrarasaVarnama Kshaudramehi (the person whose urine has taste and color like Madhu), which is similar to glycosuria in Diabetes Mellitus. Aim: The aim of this article is to describe the role of Pathya-Ahara and various Yogic practices in the management of Type-II DM. Materials and Methods: An Ayurvedic diet chart was made according to the Pathya-Ahara given in various Samhita and Yogic practices which provide benefit in diabetes according to the classical texts and various studies are described. Results: With regular practice of Asana and Pranayama along with pathya-ahara one can maintain his/her blood sugar level and if a patient is on Antidiabetic oral medicines or on insulin, their dose may be reduced or stopped. Discussion: The Asana should be practiced according to one’s power (Bala). The diet chart which is mentioned further in the article is according to Northern Indian culture. This can be modified according to the place.